(untitled) (Asian Journal of Medical and Biological Research, 2016)
Labeo bata is one of the important minor carps in Bangladesh with great demand as good table fish. The study was conducted to observe the breeding performance at different management practices in Mafatema, Rupali, Modhumoti and Anan fish hatchery and disinfection treatments of water, eggs and fry in Jessore, Bangladesh during 10 March 2014 to 15 May 2015. An improvement in broodstock nutrition and feeding has been shown to greatly improve seed production. Protein and lipid percentage of broodstock diet have been identified as major dietary factors. Protein level was 24.77%, 23.47%, 18.08%, 17.78% and lipid level was 11.07%, 9.50%, 7.74%, 8.14% in Mafatema, Rupali, Modhumoti and Anan fish hatchery respectively. Three concentrations of four chemical-formalin (10, 20, 30 mg/L), malachite green (1, 3, 5 mg/L), NaCl (1, 2, 3 g/L) and methylene blue ( 1, 3, 5 mg/L) treatment regimes and a control were compared for efficacy in treating L. bata eggs to prevent fungus and bacterial infection and improve hatch and survival rate of fry. Highest correlation value between absolute fecundity and body weight (r=.938, p<.05) and total length (r=.891, p<.05) and gonadosomatic index (26.2%) were found in Mafatema fish hatchery among four experimental hatcheries at 24.77% protein and 11.07% lipid level. Better fertilization rate (84.2±5.17%) and hatching rate (82.0±4.30%) were found in Mafatema and Rupali fish hatchery respectively that has significant difference (P<0.05) from that of Modhumoti and Anan fish hatchery at higher protein and lipid level. Lowest deformity rate (6.05+2.65) was observed in Mafatema fish hatchery that was significantly different (P<0.05) from that of Modhumoti fish hatchery. In case of disinfection treatment, methylene blue at 1mg/L bath treatment daily for 4 days showed significantly higher hatching rate (92.33±3.51%) and survival rate (94.33±4.73%). Asian J. Med. Biol. Res. December 2015, 1(3): 553-568